Impact of social determinants of health on individuals living with generalized myasthenia gravis and implications for patient support programs - Hughes, Tom; Anderson, Ashley E. L.; Habib, Ali A.; Perez, Kathy; Bergin, Cathleen; Suchotliff, Sharon; Zvosec, Cecilia; McDaniel, Dajzsa; Sato, Mai; Whangbo, Albert; Phillips, Glenn (Frontiers in Public Health, 2023)
Introduction: Social determinants of health (SDOH) are important contributors to health outcomes, and better understanding their impact on individuals diagnosed with rare, chronic diseases with high burden and unmet need is critical. Characterizing SDOH burden can help improve the design of patient support programs (PSPs), using targeted approaches to remove barriers to access. Methods: This study used a mixed-methods strategy employing a quantitative survey, which was designed based on qualitative interviews, to understand the unmet needs and awareness/utilization of PSPs among individuals living with generalized myasthenia gravis (gMG) and experiencing SDOH barriers. The survey was completed by 38 individuals living with gMG, of which the majority were non-White/Caucasian, unemployed, low income, and enrolled in public insurance. Common SDOH challenges, awareness/utilization of available PSPs, and unmet needs were identified. Results: Financial and mental health concerns were the most common among individuals living with gMG and experiencing SDOH barriers throughout diagnosis, accessing treatment, initiating treatment, and continuing treatment. Awareness and utilization of existing support services were low, especially when accessing treatment. Educational, financial, and personalized support with high “human touch” were commonly perceived as the most valuable resources. Implications: To better serve the needs of individuals with gMG experiencing SDOH barriers, PSPs should use a targeted approach to offer services tailored to harder-to-reach populations. Further, providers, advocacy groups, manufacturers, and public organizations in the gMG ecosystem should strengthen collaborations with PSPs to enable individuals living with gMG to access the services they need to improve their health outcomes.